High-Energy Blast Injury Requiring Transradial Amputation with Associated Essex Lopresti and Terrible Triad Injuries of the Elbow: A Rare Presentation. (4th March 2021) - Knapp, Paul; Powell, Dexter; Bandovic, Ivan; Coon, Matthew; Best, Benjamin
Abstract : Case . Blast injuries to the upper extremity can be devastating and emotionally stressful injuries. We describe a case of a high-energy blast injury to an upper extremity from an explosive. The transfer of energy caused severe soft tissue/bony damage to the hand, but also led to associated Essex Lopresti and terrible triad injuries. The patient required emergent transradial amputation by hand surgery as well as definitive fixation by our orthopaedic team. Conclusion . We describe a unique salvage operation that established forearm pronosupination, elbow flexion, and proper prosthetic fitting. We feel that describing our technique could help others in treating this injury if encountered.